The use of abatacept in debilitating cavitating lung disease associated with rheumatoid arthritis, bronchocentric granulomatosis and aspergillosis. Issue 6 (3rd June 2010) - Neff, K; Stack, J; Harney, S; Henry, M
Abstract : A case of debilitating cavitating lung disease associated with rheumatoid arthritis and bronchocentric granulomatosis, which failed to respond to conventional medical or surgical treatment, is described. The patient was treated over 10 years with steroids, antimicrobial agents, disease-modifying antirheumatoid drugs and surgery. Lung function continued to decline and the patient presented for admission with recurrent pneumonia. Abatacept was initiated to modify the underlying immunopathology. Following 12 months of treatment with abatacept the patient has demonstrable improvement in lung function and lung anatomy, and has not presented to hospital with pneumonia. She has tolerated the treatment without complication. The use of abatacept has stabilised the lung disease in this case in the medium term and prevented readmission to hospital. These results suggest a larger role for abatacept in those with such disease in the future and may warrant further investigation.